Detection of Candidemia in a Sample of Iraqi Neonates Admitted to the Neonates' Intensive Care Unit (NICU) by Conventional Methods (Iraqi Journal of Medical Sciences, 2024)
Background: There are many cases of neonatal intensive care unit (NICU) admission due to sepsis; many of them have bacterial sepsis, and others have a serious health risk from fungemia, particularly infections brought on by fungal infection. Numerous variables, including gestational age, birth weight, and the use of invasive medical procedures, might affect the incidence of fungemia. It is important to know how often fungemia happens in NICUs and what the risk factors are in order to improving infection control strategies and come up with effective strategies to prevent infections.Objective: To determine the prevalence of fungal infection in newborns who had risk factors by using conventional diagnostic techniques. Methods: This study included 100 newborns who were admitted into NICUs in Children Welfare Teaching Hospital and Baghdad Teaching Hospital at the period from December 2022 to the end of April 2023. They were having one or more of these risk factors; history of invasive procedures, antibiotic usage, and hospital care management techniques. Conventional blood culture procedure.Results: The findings showed that none of the newborns who were recruited had any evidence of candidemia, which was unexpected considering the known risk factors and the well-acknowledged sensitivity of these diagnostic techniques.Conclusion: Traditional diagnostic methods in neonatal candidemia detection may lack sensitivity, highlighting the potential for molecular techniques like polymerase chain reaction (PCR), though further research is warranted due to study limitations. Keywords: Candidemia, Conventional Methods, Neonatal Intensive Care Unit (NICU), RiskFactors and EfficacyCitation: Nasif MS, Al-Attraqchi AA, Mohammad AA. Detection of Candidemia in a sample of Iraqi neonates admitted to the neonates' intensive care unit (NICU) by conventional methods. Iraqi JMS. 2024; 22(1): 74-78. doi: 10.22578/IJMS.22.1.9
Keywords: Candidemia; Conventional Methods; Neonatal Intensive Care Unit NICU; Risk